(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research study was conducted by the researcher to determine and identify the effectiveness of CCTV cameras in terms of crime prevention in certain settings of Barangay Novaliches Proper. The study showed the results of the assessment based on the respondents’ feedback, which includes the surveillance process wherein the CCTV camera monitors the movement of certain perpetrators or suspects before or after committing certain crimes to track down the malicious behavior and apprehend it immediately upon using the discreet techniques and strategies of surveillance by the law enforcement personnel. The results of the study also found that CCTV cameras can be utilized for security purposes, including guarding large areas of establishments or places using CCTV cameras and monitoring the activities going in and out of certain places. Furthermore, the effectiveness of CCTV cameras in crime prevention was also described in terms of crime rate based on the respondents’ feedback, wherein it can be utilized to prevent crime from committing it, and it serves as a deterrence to establish a low chance probability of committing the crimes. Throughout the study, the researcher was able to address and determine the problems encountered in using CCTV cameras in crime prevention, such as the surveillance can violate certain provisions of the law and constitution of the Philippines to have the rights of privacy in accordance to the Republic Act 10173 the Data Privacy Act of 2012, including but not limited to, data loss by system failures which relies on Wi-Fi or power energy, image is not always clear, easy to be able to sneak from the CCTV, misuse of footage, illegal infiltration of hackers and limited of funding to upgrade the cause of high cost of maintenance.